2020
DOI: 10.1080/09540105.2020.1798885
|View full text |Cite
|
Sign up to set email alerts
|

Diazinon acute exposure induces neutrophil extracellular traps in Nile tilapia (Oreochromis niloticus)

Abstract: Diazinon is an organophosphate insecticide commonly used worldwide to chemically control different organisms considered as pests. In the past years, diazinon has been described to have immunotoxic effects in several species. Nile tilapia is a teleost fish with an ecological and economic importance, which is also one of the fishes with the highest consumption around the world. The aim of this study was to evaluate the production of neutrophil extracellular traps (NETs) from fish Nile tilapia (Oreochromis niloti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Fish neutrophils can also release NETs that function similarly to those in mammals and stimulate fish immune defenses. Until now, bacterial, 34 virus, 35 diazinon, 36 avermectin, 37 fluorine, 38 and mercury 39 have been shown to induce NET formation in fish through a variety of mechanisms. Furthermore, recent studies have shown that NET formation exacerbates liver injury in cases of ischemia/reperfusion or nonalcoholic steatohepatitis 40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…Fish neutrophils can also release NETs that function similarly to those in mammals and stimulate fish immune defenses. Until now, bacterial, 34 virus, 35 diazinon, 36 avermectin, 37 fluorine, 38 and mercury 39 have been shown to induce NET formation in fish through a variety of mechanisms. Furthermore, recent studies have shown that NET formation exacerbates liver injury in cases of ischemia/reperfusion or nonalcoholic steatohepatitis 40,41 .…”
Section: Introductionmentioning
confidence: 99%